Economic consequences of unrecorded liabilities. - Chow, Cheok Mun. (2008)
This project looks at liabilities that are only disclosed in the notes to the accounts mainly; contingent liabilities, operating lease commitments and deferred taxes and their impact on the balance sheet if they were recorded.